Analisis Efektivitas Bantuan Luar Negeri: Development Aid China pada Proyek Hydropower Bui Dam di Ghana - Satriani, Prinailla Reinata (Journal of Politics and Democracy, 2024)
China is one of the largest providers of foreign aid to African countries, one of which is Ghana. China provided funding assistance for the Bui dam hydropower project, which currently produces 730 gigawatts/hour and provides agricultural irrigation for approximately 30,000 hectares. However, during the construction period, this project required Ghanaians living around Bui to move their settlements and there were problems with workers from Ghana. This research aims to analyze the effectiveness of China's foreign assistance in the Bui dam hydropower project in Ghana with various existing controversies. The author uses descriptive qualitative methods as a research method to answer the big research questions. With the results of such research, the Bui dam project is quite effective in terms of the effectiveness of foreign aid based on the principles of the Paris Declaration, but still shows room for continuous improvement in terms of transparency, labor rights and project monitoring.